Fabrication and antimicrobial analysis of composite biodegradable film from breadfruit - Shahaidah, Shariff (2010)
This study will be focusing on fabrication and antimicrobial analysis of composite biodegradable film from breadfruit starch-chitosan. The films were characterized in terms of physical, chemical and also the antimicrobial analysis. The antimicrobial effect of composite films was tested on Bacillus substilis (B.substilis) and Eschericha coli (E.coli) represent Gram-positive bacteria and Gram-negative bacteria respectively. The sample was prepared by cutting each sample into 2cm x 2cm and were placed into solid media that bacterial growth plate. Inhibition of bacterial growth was examined using zone inhibition method on solid media.The composite biodegradable film were characterized by fourier transform infrared spectroscopy (FTIR) analysis by preparing the sample with 1cm x 1 cm and revealed the spectrum of composite film containing chitosan and breadfruit starch at peak shifted from 3100 cm-1 to 3400 cm -1 due to hydroxyl stretching interactions. The amino acid group peak of chitosan at bands 1650.40 cm -1. The composite biodegradable film also undergoes scanning electron microscopy (SEM) to characterize the morphology of the films with scan area of 0.3cm x 6cm. The cross section of the composite film shown distinctive film structure. Furthermore, water solubility also tested by cutting the each sample into 5cm x 5 cm and were dried at 70°C in a vacuum oven for 24 hours to constant weight. The sample films was immersed into 20ml of distilled water and placed into 50ml screw cap tubes and gently shaking for 24 hours . The result expose the decreasing percentage of water solubility by the addition of chitosan. Tensile strength (TS) and Elongation (E) break also tested and the result shows that TS inversely proportional to E. Degradation analysis also expose the film degrade under soil condition. Moreover, the characterization of breadfruit flour also characterized in terms of their structure.